ETOS KERJA PELAJAR MUSLIM DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI - Harmi Tursih; Suyadi Suyadi; Unik Hanifah Salsabila; Muh. Alif Kurniawan (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The research entitled "The Work Ethic of Muslim Students in the Novel Negeri 5 Menara by Ahmad Faudi" was conducted with the aim of analyzing the hard work ethic of Muslim students contained in the novel Negeri 5 Menara by Ahmad Fuadi and the inspiration for the hard work ethic of Muslim students contained in the novel Negeri. 5 Towers by Ahmad Fuadi for Muslim students in today's modern era. In this study, the author uses a type of library research with a semiotic approach. In this study, the authors look for signs from the novel Negeri 5 Menara that show the work ethic of Muslim students. The source of data in this study comes from primary data sources, namely the novel Negeri 5 Menara by Ahmad Fuadi, while the secondary data sources used are books and journals that are relevant to the work ethic of Muslim students. The data collection methods used are heuristic methods and hermeneutic methods. For the data analysis method, the author uses content analysis in the form of data reduction, data presentation, and drawing conclusions. Based on the research that has been done, the conclusions are as follows: 1) The work ethic of Muslim students contained in the novel Negeri 5 Menara in achieving their dreams includes discipline, respect for time, never give up, sincere, thirst for knowledge, and is future-oriented. 2) The inspiration for the hard work ethic of Muslim students contained in the novel Negeri 5 Menara by Ahmad Fuadi with Muslim students in today's modern era a) The spirit of pursuing full scholarships to study abroad and preparing the necessary requirements such as mastery of foreign languages. b) Dare to wander far from home to study. c) Dare to work at a young age and never give up.